Venue Safety Strategies: Guardrails and the Line-of-Sight Exemption - Gil Fried; Aneurin Grant (Journal of Applied Sports Management, 2023)
This piece represents a focused article on safety issues connected to railings at sporting events and why there needs to be considerable action taken to protect fans. Specifically, the authors believe the current line-of-sight exception (minimum 26") allows for railings that are dangerously inadequate to protect fans. It is argued that if sport facility managers and or venues do not proactively address this railing height issue, then architects, building inspectors, and others should seek to change the building code to eliminate the fans continued exposure to unnecessary hazards.
Keywords: Facility Design; Operation Management; Protection; Security; Sport Facilities